Meeting Energy and Nutrient Needs of Postnatal Women in Tarak Tradition - Astutik Pudjirahaju; AAG Anom Aswin; Dwie Soelistyorini (Humanistic Network for Science and Technology (HNST), 2018)
This study was aimed at analyzing the provision of energy and nutrient needs of postnatal in Tarak tradition (food abstinence) and to enhance the technical personnel role on lactation management in exclusive breastfeeding practices. This study applied qualitative design with phenomenological approach as the first phase by involving women in mountain communities of Trenggalek who undergo three consecutive phases, namely third trimester, postnatal, and breastfeed for 6 months. While on the second phase (quasi experimental) was deployed to identify the provision of energy and nutrition of postnatal women in Tarak tradition and enhancing the technical personnel role of lactation management. The results showed that the respondents in mountain area of Bendungan Subdistrict, Trenggalek Regency committed to practice Tarak during pregnancy and postnatal. The belief of eating pineapple that would cause miscarriage was the most common practice of it. The other practices are dietary restrictions of banana and tape (fermented cassava). Interventions through counseling on balanced nutrition and supplementary feeding for replenishing energy by 331 calorie/day and 19 gram/day protein for 30 days had a significant effect on weight gain and nutritional status measured with LILA (upper arm circumference). The increased weight and nutritional status indicated success in breastfeeding. Furthermore, this study also revealed the success of 6 months exclusive breastfeeding practice. Enhancing the technical personnel role on lactation management brought a significant effect on the raise of exclusive breastfeeding practices. Keywords: Tarak, Lactation management, Exclusive breastfeeding